A New Mixed Estimator in Nonparametric Regression for Longitudinal Data - Made Ayu Dwi Octavanny; I Nyoman Budiantara; Heri Kuswanto; Dyah Putri Rahmawati (Journal of Mathematics)
We introduce a new method for estimating the nonparametric regression curve for longitudinal data. This method combines two estimators: truncated spline and Fourier series. This estimation is completed by minimizing the penalized weighted least squares and weighted least squares. This paper also provides the properties of the new mixed estimator, which are biased and linear in the observations. The best model is selected using the smallest value of generalized cross-validation. The performance of the new method is demonstrated by a simulation study with a variety of time points. Then, the proposed approach is applied to a stroke patient dataset. The results show that simulated data and real data yield consistent findings.